Exploring The Potential Of Saw Dust As Internal Curing Agent In Concrete Subjected To Different Curing Conditions - Ng, Shi Kin (Universiti Sains Malaysia, 2021)
In this study, the properties of concrete containing internal curing agent under different curing conditions were investigated. Saw dust is a waste material generated as a byproduct from the wood related industries. The saw dust was pre-saturated to act as an internal curing agent and silica fume was added in this research. The internal curing agent (saturated saw dust) was used to partially replace 2.5%, 5.0% and 7.5% of volume of sand and 15% silica fume was incorporated as partial replacement of the mass of cement. The water/cement ratio used in this research is 0.5. The concrete samples were subjected to three different curing conditions (water tank, dry curing room at room temperature and 40°C oven) after demoulding. From the results, the workability of concrete increases with the use of saturated saw dust. The inclusion of silica fume in internally cured concrete reduced the workability and increases the porosity. However, the compressive strength of the concrete and impermeability of concrete were improved with the use of silica fume. The optimum saw dust content found in this study was 2.5%. It was found that under curing with external water supply, the concrete with 2.5% of saturated saw dust could achieve the target strength of 40MPa. It was found that the compressive strength of 2.5% saw dust concrete was comparable to the control sample under dry curing and 40°C oven condition. Despite the observed increase in porosity with the percentage of saw dust, the permeability of the concrete with 2.5% saw dust was significantly lower than the control mix under adverse curing condition with no external curing water supply. As a conclusion, 2.5% of saturated saw dust can be applied as a cost-effective internal curing material to produce a durable concrete where wet curing is not applied.